(untitled) (Research, Society and Development, 2020)
This study evaluated the use of an edible coating alginate-based with essential oil (cinnamon and marjoram) on the quality of Wagyu hamburgers (pH, weight loss, cooking loss, texture, color, lipid oxidation and antioxidant activity) during 7 days of display. Microscopy, FTIR and acceptability were also evaluated. Four treatments were evaluated: CON –hamburger without edible coating; ECO –with edible coating; CIN –with edible coating containing 0.1% of cinnamon essential oil; MAJ –with edible coating containing 0.1% of marjoram essential oil. pH of the samples was maintained throughout the storage time (p>0.05). Coatings decreased water and color losses, and shear force in relation to CON. The results indicated that CIN presented the highest antioxidant activity (p<0.001). Malonaldehyde value increased for all samples of during storage (p<0.001), being more accentuated for CON. The CIN presented best results in the majority of the analyzes, which indicates that the use of the cinnamon essential oil in coating can increase/maintain the quality of hamburgers during display.